The Effect of CSR, Executive Risk Preference, and Company Size on Tax Avoidance in Financial Institutions in Indonesia - Ghina Kemala Dewi; Alvi Darmawati Nur Hardaningrum; Satiti Utami; Pandu Adi Cakranegara (PT Mattawang Mediatama Solution, 2022)
This research aims to analyze CSR, Executive Risk Preference and Company Size on tax avoidance in Indonesia. This study is quantitative research, where the dependent variable is tax avoidance. To proxy tax avoidance, it uses a cash-effective tax rate (CETR). Independent variables examined include Corporate Social Responsibility, Executive Risk Preference and Firm Size. The sample of this study was 55 companies in the Financial Financing Institution sector, listed on the Indonesia Stock Exchange during period 2015-2019. This study uses purposive sampling to determine samples with predetermined criteria. At the same time, a classical assumption test is used to analyze the data. Hypothesis testing is performed using multiple linear regression methods. The results show that Corporate Social Responsibility and Company Size have a significant positive effect on tax avoidance. In contrast, there is no significant positive effect of Executive Risk Preference on tax avoidance.